2014
DOI: 10.1111/all.12562
|View full text |Cite
|
Sign up to set email alerts
|

Total serum IgE level influences oral food challenge tests for IgE‐mediated food allergies

Abstract: Probability curves predicting oral food challenge test (OFC) results based on specific IgE levels are widely used to prevent serious allergic reactions. Although several confounding factors are known to affect probability curves, the main factors that affect OFC outcomes are currently unclear. We hypothesized that an increased total IgE level would reduce allergic reactivity. Medical records of 337 and 266 patients who underwent OFCs for 3.5 g boiled hen's egg white and 3.1 ml raw cow's milk, respectively, wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 16 publications
2
22
3
Order By: Relevance
“…After our multivariate analyses were adjusted by statistically significant patient factors, total IgE was no longer significant. Low total IgE levels were reported as a risk factor for positive OFC in milk and whole‐egg OFC , in contrast with our findings for heated egg yolk OFC.…”
Section: Discussioncontrasting
confidence: 99%
“…After our multivariate analyses were adjusted by statistically significant patient factors, total IgE was no longer significant. Low total IgE levels were reported as a risk factor for positive OFC in milk and whole‐egg OFC , in contrast with our findings for heated egg yolk OFC.…”
Section: Discussioncontrasting
confidence: 99%
“…Our observation that egg‐tolerant (as opposed to egg‐allergic) individuals have higher total IgE levels, which correlate strongly with sIgE, supports the hypothesis that higher total IgE titres might contribute to elevated but clinically irrelevant sIgE levels. In agreement, in a recent study, children with the highest total IgE levels (>75th centile) were less responsive in challenges to cow's milk and egg than those with lower total IgE, even for similar values of sIgE . Federly et al.…”
Section: Characteristics Of Subjects Recruited and Comparative Analyscontrasting
confidence: 62%
“…Total IgE might cause artefactual elevation of sIgE levels, possibly leading to misdiagnosis of food allergy. Although a study published 10 years ago reported that the egg‐sIgE/total IgE ratio was not superior to sIgE alone in young children with suspected egg allergy , more recent evidence suggests that total IgE influences allergen‐sIgE levels and challenge outcome . Accordingly, the sIgE/total IgE ratio was found to have better diagnostic performance than sIgE alone for persistent food allergens – particularly for nuts .…”
Section: Characteristics Of Subjects Recruited and Comparative Analysmentioning
confidence: 99%
“…However, a diagnosis of allergic rhinitis is best supported by the detection of specific IgE to allergens relevant to the clinical history. Third, in patients with food allergies, the ratio of allergen‐specific IgE to total serum IgE has predictive value for outcomes of oral food challenges …”
Section: Conditions Associated With Total Serum Ige >1000 Iu/mlmentioning
confidence: 99%